2018
DOI: 10.12659/msm.909144
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Inhibits HeLa Cells by Impairing Autophagic Flux via AMP-Activated Protein Kinase (AMPK) Activation and Endoplasmic Reticulum Stress Regulated by Calcium

Abstract: BackgroundPropofol has antitumor effects against various cancers. However, the mechanism of action of propofol in HeLa human cervical cancer cells has not been elucidated.Material/MethodsWe treated HeLa human cervical cancer cells with different concentrations of propofol. Cell viability was evaluated with Cell Counting Kit-8 and apoptosis was analyzed by annexin V-fluorescein isothiocyanate and propidium iodide staining and flow cytometry. Autophagosome formation was evaluated based on microtubule-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
(54 reference statements)
1
15
0
Order By: Relevance
“…Propofol, a central nervous system anesthetic, is often used in surgical operations in combination with inhalational anesthetics and analgesics. in addition to its function as an anesthetic, the antitumor effects of propofol have been demonstrated in gastric, lung, cervical and breast cancer (9)(10)(11)(12). a previous study reported that propofol inhibited the invasion of ovarian cancer cells and enhanced the apoptotic effect of paclitaxel on ovarian cancer cells (13); however, the molecular mechanisms underlying these specific roles of propofol in ovarian cancer are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Propofol, a central nervous system anesthetic, is often used in surgical operations in combination with inhalational anesthetics and analgesics. in addition to its function as an anesthetic, the antitumor effects of propofol have been demonstrated in gastric, lung, cervical and breast cancer (9)(10)(11)(12). a previous study reported that propofol inhibited the invasion of ovarian cancer cells and enhanced the apoptotic effect of paclitaxel on ovarian cancer cells (13); however, the molecular mechanisms underlying these specific roles of propofol in ovarian cancer are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These results clearly show that AMPK is activated by metformin even in the deficiency of LKB1. Kinases other than LKB1, namely CAMKK, ATM, and TAK1 have been reported to be able to activate AMPK (Sun et al, 2007;Herrero-Martin et al, 2009;Sanli et al, 2010;Gou et al, 2013;Fogarty et al, 2016;Loubiere et al, 2017;Chen et al, 2018). LKB1 can act as a low energy sensor and acts as a negative regulator of apoptosis in normal cells (Shaw et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that propofol suppresses the proliferation, differentiation, and migration of neural stem cells (NSCs), and these functions are partially mediated by the calmodulin-dependent protein kinase (CaMk) II/phosphorylation of serine at amino acid position 485 (pS485)/AMPK/activating transcription factor 5 (ATF5) signaling pathway (41). Importantly, the AMPK/ mTOR signaling pathway has been found to be activated in propofol-induced autophagosome accumulation in HeLa cells (42). Medium-and long-chain triglyceride (MCT/LCT) propofol not only significantly promotes the phosphorylation of AMPK and acetyl coenzyme A carboxylase (ACC), but also reverses the free fatty acid (FFA)-induced decreased phosphorylation of AMPK and ACC (43).…”
Section: Discussionmentioning
confidence: 99%